Mothers’ practices in children’s dental health and early childhood caries: A scoping review - Zia, Hanim Khalida; Syah, Nur Afrainin; Machmud, Rizanda; Kasuma, Nila; Dasman, Hardisman; Mona, Deli; Purna, Rozi Sastra; Bachtiar, Adang (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRAKIntroduction: The World Health Organization (WHO) in 2022 reported that dental and oral diseases affect approximately 3.5 billion people globally, including 2 billion adults and 514 million children suffering from dental caries. Dental caries occurring in early childhood is known as Early Childhood Caries (ECC). This study aims to identify mothers' practices on children's dental health and early childhood caries. Methods: This study used a scoping review method. The article selection was conducted by searching the PubMed and ScienceDirect databases using the keywords Knowledge, Attitude, Practice, Mother, Early Childhood Caries. Articles were screened according to inclusion and exclusion criteria, titles, abstracts, and content relevance, resulting in 21 studies included for review. Data were analyzed using Exploratory Data Analysis (EDA) to identify maternal practices related to children's dental health and early childhood caries. Results: This study showed that mothers' practices in children's dental health and early childhood caries consisted of three main areas: maintaining oral health, feeding practices, and prevention of bacterial transmission. Maintaining oral health, included seeking information on oral health, taking children to the dentist, assisting them with brushing using fluoride toothpaste, replacing toothbrushes regularly, brushing the tongue, using dental floss for children, and encouraging rinsing after eating. Feeding practices involved frequently giving children sweet foods and drinks, breastfeeding at night, providing formula milk, and giving milk bottles. Prevention of bacterial transmission included maintaining oral health during pregnancy and pre-chewing food before feeding the child. Conclusion: Mothers’ practices in children's dental health and early childhood caries primarily involve oral health maintenance, feeding management, and prevention of bacterial transmission.KEY WORDS: knowledge, attitude, practice, mother, early childhood cariesPraktik ibu dalam kesehatan gigi anak dan early childhood caries: Scoping reviewABSTRACTPendahuluan: World Health Organization (WHO) tahun 2022 menyatakan penyakit gigi dan mulut memengaruhi 3,5 miliar orang di seluruh dunia. Sebanyak 2 miliar orang dewasa dan 514 juta anak menderita karies gigi. Karies gigi pada usia dini disebut Early Childhood Caries (ECC). Tujuan penelitian ini menganalisis praktik ibu dalam kesehatan gigi anak dan early childhood caries. Metode: Penelitian ini menggunakan metode scoping review. Proses seleksi artikel dilakukan pencarian artikel menggunakan kata kunci Knowledge, Attitude, Practice, Mother, Early Childhood Caries pada database PubMed dan Science Direct, penyaringan berdasarkan kriteria inklusi, eksklusi, judul, abstrak, dan isi yang sesuai topik didapatkan 21 artikel untuk di review. Data dianalisis dengan cara Eksplorasi Data (EDA) untuk mengetahui apa saja praktik ibu dalam kesehatan gigi anak dan early childhood caries. Hasil: Penelitian ini menunjukkan praktik ibu dalam kesehatan gigi anak dan early childhood, yaitu pemeliharaan kesehatan gigi dan mulut, meliputi mencari informasi kesehatan gigi dan mulut anak, membawa anak ke dokter gigi, mendampingi anak menyikat gigi, memberi anak pasta gigi berfluoride, mengganti sikat gigi anak, menyikat lidah anak, menggunakan benang gigi untuk anak, dan membiasakan anak berkumur setelah makan. Pemberian makanan, meliputi sering memberi anak makanan manis, sering memberi anak minuman manis, sering memberi ASI anak malam hari, memberi anak susu formula, dan memberi anak botol susu. Pencegahan transmisi bakteri, meliputi menjaga kesehatan gigi ketika hamil dan mengunyahkan makanan anak. Simpulan: Penelitian ini menyimpulkan praktik ibu dalam kesehatan gigi anak dan early childhood caries yaitu pemeliharaan kesehatan gigi dan mulut, pemberian makanan, serta pencegahan transmisi bakteri.KATA KUNCI: pengetahuan, sikap, praktik, ibu, early childhood caries